THE FACTORS THAT INFLUENCE CONSUMER SATISFACTION ON GOPAY - Azmy, Ahmad; Subakrie, Pitrayadi; Azhari, Muhammad Zakky (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2020)
This research aims to analyze the factors that influence consumer satisfaction on Go-Pay as a mobile payment application. The population of this research was all Gojek application users who use Go-Pay as mobile payment in South Jakarta. This research used primary data sourced from the questionnaire distributed to 150 respondents. Data were analyzed using multiple linear regression analysis. The results showed that four independent variables, i.e., price, trust, lifestyle, and benefit have a significant influence on consumer satisfaction of Go-Pay application. However, convenience has no significant influence on consumer satisfaction of Go-Pay. Keywords: consumer satisfaction, Go-pay, lifestyle